2022
DOI: 10.1001/jama.2022.4315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Corticosteroid Dosing Regimens on Clinical Outcomes in Boys With Duchenne Muscular Dystrophy

Abstract: Key PointsQuestionWhat is the difference in clinical outcomes among 3 corticosteroid regimens (0.75 mg/kg of daily prednisone, 0.90 mg/kg of daily deflazacort, or 0.75 mg/kg of intermittent prednisone for 10 days on and then 10 days off) as initial treatment for boys with Duchenne muscular dystrophy?FindingsThis randomized clinical trial included 196 boys with Duchenne muscular dystrophy; the clinical outcome was a global outcome that incorporated a measure of rising from the floor, forced vital capacity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 44 publications
6
59
0
1
Order By: Relevance
“…In contrast, PRED stunted growth from 12-14 days (Supp Fig 1A), increased water consumption between 10-11 days (Supp Fig 1C) and reduced spleen mass (data not shown). Our data are consistent with the known growth inhibiting, mineralocorticoid, and immunosuppressive side-effects of PRED treatment in children (20).…”
Section: Resultssupporting
confidence: 90%
“…In contrast, PRED stunted growth from 12-14 days (Supp Fig 1A), increased water consumption between 10-11 days (Supp Fig 1C) and reduced spleen mass (data not shown). Our data are consistent with the known growth inhibiting, mineralocorticoid, and immunosuppressive side-effects of PRED treatment in children (20).…”
Section: Resultssupporting
confidence: 90%
“…In a recently published individual patient data meta‐analysis including only the placebo arm patients of an RCT, deflazacort was superior to prednisone in slowing disease progression as measured by the 6‐minute walk test at 48 weeks 37 . Although our analysis showed that deflazacort may be inferior in preventing decline in pulmonary function and was associated with more adverse events, a recently published large prospective RCT found daily deflazacort to be equally effective to daily prednisone for motor function, pulmonary function, and satisfaction with treatment 38 . Both were superior to intermittent prednisone alternating 10 days on and 10 days off over a 3‐y follow‐up when assessed by composite outcome comprising measures of motor function, pulmonary function, and satisfaction with treatment 38 .…”
Section: Discussionmentioning
confidence: 59%
“…38 Both were superior to intermittent prednisone alternating 10 days on and 10 days off over a 3-y follow-up when assessed by composite outcome comprising measures of motor function, pulmonary function, and satisfaction with treatment. 38 For several recommendations, we found no or insufficient evidence, thus indicating a need for further studies. For example, fusion surgery in scoliosis may have preserved pulmonary function in uncontrolled trials but no RCTs are available.…”
Section: Predictors For Mortalitymentioning
confidence: 97%
“…Currently, there is no effective cure for DMD. Clinical treatment with glucocorticoids delays the disease progression but does not alter the outcome of the disease [4]. Long-term treatment requires correction of the gene defect or compensation of the dystrophin gene function.…”
Section: Introductionmentioning
confidence: 99%